Crustal structure and tectonic evolution of the Newfoundland Ridge, Fogo Basin, and southern Newfoundland transform margin. (September 2022) - Cawood, Adam J.; Ferrill, David A.; Norris, David; Bowness, Nina P.; Glass, Elliott J.; Smart, Kevin J.; Morris, Alan P.; Gillis, Erin
Abstract: The southern Newfoundland transform margin is a crustal-scale transfer zone that juxtaposes continental crust of the Grand Banks with the oceanic domain of the Fogo Basin, offshore SE Newfoundland. This crustal feature is generally accepted as a left-lateral transfer zone between the much-studied Scotian and Newfoundland margins, but relatively little is known about either its crustal-scale architecture or tectonic evolution. Interpretation of newly available regional seismic data from the Newfoundland Ridge and Fogo Basin, offshore Canada provides evidence for approximately 500 km of left-lateral displacement and associated segmented extension between the Late Triassic (210 Ma) and latest Jurassic (145 Ma) as a result of differential extension rates between the conjugate margins of Nova Scotia–Morocco and Newfoundland (Grand Banks)–Iberia. We show that the southern Newfoundland transform margin represents a 100–150 km wide zone of distributed left-lateral displacement across extended continental crust at the SW edge of the Grand Banks, and that crust beneath the Newfoundland Ridge and Fogo Basin is unlikely to be oceanic in origin. Kinematic restorations of regional cross sections and crustal area balancing provide the basis for map-based reconstructions of the area. Our results, which integrate existing plate reconstructions, crustal thickness data, and established age relationships, help to constrain the early structural evolution of the North Atlantic as the African and North American plates separated during Triassic to Jurassic rifting. Highlights: The southern Newfoundland transform margin represents a 100–150 km wide zone of distributed left-lateral displacement. Differing extension rates between Nova Scotia–Morocco and Newfoundland–Iberia led to continental transform margin. The Fogo Basin and Newfoundland Ridge are underlain by extended continental crust. Diapirism of syn-rift Triassic evaporites is documented throughout the study area. Diapirs formed as a result of primarily vertical salt movement from grabens and half-grabens in extended continental crust.